Effect of Artemisia campestris on the health of living beings - Cherfi Inasse (Universty Of El-oued جامعة الوادي, 2025)
Artemisia campestris L. is a medicinal plant known for its antioxidant and anti-inflammatory properties. However, its therapeutic potential in endocrine disorders, particularly polycystic ovarian syndrome (PCOS) and hypothyroidism, remains underexplored. This study investigates the biological activities of its aqueous extract and essential oil, evaluating their efficacy in managing these conditions. Fifteen mature Wistar rats were divided into three groups: control, PCOS-induced, and a PCOS group treated with 200 mg/kg A. campestris L. extract for 15 days. Treatment significantly reduced luteinizing hormone (LH) levels and improved ovarian histomorphometry. In a hypothyroidism model induced by Carbimazole, both the aqueous extract and essential oil (administered at 200 mg/kg BW) enhanced thyroid function, as indicated by increased FT4 and decreased TSH levels. The aqueous extract exhibited strong antioxidant activity, with IC50 values of 4.34 µg/mL (DPPH°), 6.19 µg/mL (FRAP), and 3.27 µg/mL (β-carotene). It also demonstrated notable α-amylase inhibitory activity (IC50 = 2.418 µg/mL). Histopathological analysis confirmed the protective effects on thyroid tissue morphology. Chemical characterization using ultra-performance liquid chromatography (UPLC) and gas chromatography-mass spectrometry (GC-MS) identified key bioactive compounds. The aqueous extract contained β-sitosterol (14.3 µg/mL), Arteannuin B (12.6 µg/mL), Scopoletin (8.22 µg/mL), Artemisinin (6.13 µg/g), and Rutin (5.8 µg/mL). GC-MS analysis of the essential oil revealed major constituents, including linalyl acetate (2.92%), geranyl acetate (2.45%), cyclononasiloxane (2.37%), cyclohexanol (1.76%), and eucalyptol (1.38%). The essential oil exhibited potent antioxidant activity (IC50 = 11.09 µg/mL for DPPH°, 15.81 µg/mL for FRAP, and 22.70 µg/mL for β-carotene) and inhibited peroxidase activity by 62% and 50%. In silico molecular docking studies supported these findings, revealing strong interactions between the identified compounds and thyroperoxidase, a key enzyme for thyroid function. Additionally, 3-cyclopentyl-N-(2-(3.4-dimethoxyphenyl)ethyl) was identified as a potential candidate for pancreatic cancer therapy due to its high binding affinity to cancer receptors. These findings highlight the therapeutic potential of A. campestris L. in managing PCOS and hypothyroidism, with its aqueous extract and essential oil demonstrating significant endocrine-modulating, antioxidant, and anti-inflammatory properties. The molecular docking results further suggest possible applications in cancer therapy, warranting further investigation into its pharmacological benefits. تعتبر Artemisia campestris L نبتة طبية معروفة بخصائصها المضادة للأكسدة والمضادة للالتهابات. ومع ذلك، فإن إمكانياتها العلاجية في اضطرابات الغدد الصماء، وخاصة متلازمة تكيس المبايض (PCOS) وقصور الغدة الدرقية، لا تزال غير مستكشفة بشكل كافٍ. تهدف هذه الدراسة إلى تقييم الأنشطة البيولوجية لمستخلصها المائي وزيتها العطري، وقياس فعاليتها في إدارة هذه الحالات .تم تقسيم خمسة عشر جرذًا ناضجًا من نوع ويستار إلى ثلاث مجموعات: مجموعة شاهدة، مجموعة مصابة بمتلازمة تكيس المبايض، ومجموعة مصابة تم علاجها بـ 200 ملغ/كغ من مستخلص A. campestris لمدة 15 يومًا. أدى العلاج إلى انخفاض ملحوظ في مستويات هرمون (LH) وتحسين الهيكل النسيجي للمبيض. وفي نموذج قصور الغدة الدرقية المستحث بواسطة الكاربيمازول، تم تقييم التأثيرات الوقائية لكل من المستخلص المائي والزيت العطري عند جرعة 200 ملغ/كغ من وزن الجسم، مما أظهر تحسنًا في وظائف الغدة الدرقية كما يتضح من ارتفاع مستويات FT4 وانخفاض .TSHأظهر المستخلص المائي نشاطًا مضادًا للأكسدة بدرجات IC50 بلغت 4.34 ميكروغرام/مل (DPPH°)، 6.19 ميكروغرام/مل (FRAP)، و3.27 ميكروغرام/مل (β-carotene). كما أظهر نشاطًا مثبطًا ملحوظًا لإنزيم α- amylase بقيمة IC50 = 2.418 ميكروغرام/مل. أكدت التحليلات النسيجية التأثيرات الوقائية على بنية الغدة الدرقية. تم تحديد المركبات النشطة بيولوجيًا من خلال التحليل الكيميائي باستخدام كروماتوغرافيا السائل عالية الأداء (UPLC) وكروماتوغرافيا الغاز-مطياف الكتلة (GC-MS). احتوى المستخلص المائي على بيتا-سيتوستيرول 14.3 ميكروغرام/مل أرتينوين ب 12.6 ميكروغرام/مل، سكوبوليتين 8.22 ميكروغرام/مل، أرتيميسينين 6.13 ميكروغرام/غ، وروتين 5.8 ميكروغرام/مل. أما تحليل GC-MS للزيت العطري فقد كشف عن مركبات رئيسية مثل أسيتات الليناليل (2.92%)، أسيتات الجيرانييل (2.45%)، سيكلونوناسيلوكسين (2.37%)، سيكلوهكسانول (1.76%)، والأوكاليبتول (1.38%). كما أظهر الزيت العطري نشاطًا مضادًا للأكسدة بقيم IC50 بلغت 11.09 ميكروغرام/مل (DPPH°)، 15.81 ميكروغرام/مل (FRAP)، و22.70 ميكروغرام/مل (β-carotene)، بالإضافة إلى تثبيط نشاط البيروكسيداز بنسبة 62% و50%. أكدت دراسات الارتباط الجزيئي (In Silico Molecular Docking) هذه النتائج، حيث كشفت عن تفاعلات قوية بين المركبات النشطة المحددة وإنزيم ثايرو بيروكسيداز، وهو إنزيم رئيسي في وظيفة الغدة الدرقية. بالإضافة إلى ذلك، تم تحديد المركب 3-cyclopentyl-N-(2-(3,4-dimethoxyphenyl)ethyl) كمرشح واعد لعلاج سرطان البنكرياس نظرًا لارتباطه القوي بمستقبلات السرطان. تؤكد هذه النتائج الإمكانات العلاجية الكبيرة لنبتة A. campestris L. في إدارة متلازمة تكيس المبايض وقصور الغدة الدرقية، حيث أظهر مستخلصها المائي وزيتها العطري خصائص هامة مضادة للأكسدة ومضادة للالتهابات ومنظمة لوظائف الغدد الصماء. كما تشير نتائج الارتباط الجزيئي إلى إمكانية استخدامها في علاج السرطان، مما يستدعي مزيدًا من البحث حول فوائدها الدوائية.
في علوم الطبيعة و الحياة Applied Biochemistry أطروحة دكتوراه تخصص
Keywords: Artemisia campestris L; Polycystic ovary syndrome; Hypothyroidism; Essential oil; Aqueous extract; Molecular docking; Antioxidant activity; Anti-inflammatory properties; GC-MS; UPLC; α-amylase inhibition; pancreatic cancer; ، متلازمة تكيس المبايض، قصور الغدة الدرقية، الزيت العطري، المستخلص المائي، الارتباط الجزيئي، النشاط المضاد للأكسدة، الخصائص المضادة للالتهابات، GC-MS، UPLC، تثبيط α-amylase، سرطان البنكرياس.